2014
DOI: 10.1111/pbaf.12036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Federal Funding on Faith‐Based and Community Organization Program Spending

Abstract: This study examines the impact of federal funding levels on the program spending of faith-based and community organizations in Kentucky. Prior research indicates that organizations could increase spending on overall program expenses or decrease program spending relative to administrative costs as a result of greater reporting demands from federal funders. Three models of program spending are proposed: increased program spending relative to administrative costs (program enhancement effect), decreased program sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 29 publications
0
9
0
14
Order By: Relevance
“…With the savings from administrative and fundraising expenditures, nonprofits could devote more resources to mission‐related outputs. In addition, Sloan and Grizzle () and Thornton () directly tested the relationship between government funding and nonprofit program spending. Sloan and Grizzle found that faith‐based and community‐based organizations in Kentucky receiving higher levels of federal grants have increased program spending.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With the savings from administrative and fundraising expenditures, nonprofits could devote more resources to mission‐related outputs. In addition, Sloan and Grizzle () and Thornton () directly tested the relationship between government funding and nonprofit program spending. Sloan and Grizzle found that faith‐based and community‐based organizations in Kentucky receiving higher levels of federal grants have increased program spending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One strand within the government-nonprofit relations literature examines the impact of government funding on nonprofits' program spending (e.g., Alexander et al, 1999;Sloan & Grizzle, 2014;Thornton, 2014). Generally, nonprofits' expenses serve three major functions: program services, internal administration, and fundraising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 On the other hand, public funding clearly increases resources of FBOs, helping them expand their services to a variety of audiences. 29 Moreover, it is arguable that public funding enhances social acceptability and legitimacy of FBOs among their private donors since receiving institutional financial support can be viewed as indicative of well-developed operational and service delivery capacity.…”
Section: Hypotheses On Raising Unrestricted Funds and Engaging In Advmentioning
confidence: 99%
“…Federal funding may also encourage the legitimacy of a faith-based organization in the eyes of other donors and therefore may be the catalyst for more private giving (Smith & Gronbjerg, 2006). While many faith-based organizations welcome these funds to help accomplish and sustain their missions, Sloan and Grizzle (2014) said "they are most often accompanied by increased reporting and evaluation requirements that tax organizational infrastructure, essentially increasing administrative responsibilities that can take time away from program activities" (p. 45). Because of the potential for government influence by having to process enormous amounts of paperwork to comply with restrictions in allocating government funds, faith-based organizations, as Tanner (2001) has explained, "may end up spending more time reading the Federal Register than the Bible" (p. 1).…”
Section: Mission Driftmentioning
confidence: 99%